FRI0609 Fifteen-Year Trend in Information on The Internet for Patients with Rheumatoid Arthritis: Evolving, but with Opportunities for Improvement. (15th July 2016) - Castillo-Ortiz, J.D.; Valdivia-Nuno, J.D.J.; Ramirez-Gomez, A.; Castaneda-Sanchez, J.J.; Sanchez-Gonzalez, J.M.; Ramos-Remus, C.
Abstract : Background: Rheumatoid arthritis (RA) may lasts for decades, so patient education is very important. There has been an increase in RA patients seeking information on the Internet during the last 15 years. Objectives: a) To assess the content, authorship, scope, readability and quality of the information currently available on the Internet in relation to RA; b) To compare it with a report published in 2001 [1] (2001-referent study); c) To assess the current positioning of websites posted by universities, hospitals, and medical associations. Methods: We recreated the method used for the 2001-referent study assessing information on the Internet using the phrase "rheumatoid arthritis" in WebCrawler. All websites and pages were critically assessed for relevance, scope, authorship, type of publication, and financial objectives. Differences between studies were considered significant if 95% confidence intervals did not overlap. Additionally, we added a Google search following the same method, with a particular assessment of Internet pages posted by medical institutions regarding content quality (DISCERN instrument), readability (Flesch-Kincaid Grade Level test), and accessibility (the order of appearance). Results: The search returned 316 hits using WebCrawler (85% were considered relevant). There were significant differences between the current studies and the 2001-referent studies (WebCrawler). There were increases in information sites (82% vs. 36%) and RA-specific discussion pages (59% vs. 8%), and decreases in advertisements (2% vs. 48%) and alternative therapies (27% vs. 45%). Google searches had significantly lower relevance (58% vs. 85%), more news articles (18% vs. 7%), more "only RA discussed" pages (76% vs. 59%), and less "alternative therapy" pages (19% vs. 27%) when compared with WebCrawler. Concerning the content quality of Internet pages, 37% were rated as good and 36% unbiased. Among the first 300 hits, 30 (10%) were posted by medical institutions, 17 from the United States, five from the United Kingdom, four from Australia, and one each from Canada, Malaysia, Spain and the Netherlands. The Mayo Clinic appeared as the top result, the Arthritis Foundation (United States) 3rd, the National Institute of Arthritis and Musculoskeletal and Skin Diseases (United States) 7th, the American College of Rheumatology 8th, and the Arthritis Research (UK) in 14th position. Regarding readability, 7% of these Web pages required six years of schooling, 27% between seven and nine years, 27% between 10 and 12 years, and 40% 12 years of schooling or more. Conclusions: It seems that information on the Internet has evolved in this fifteen-year period. Medical institutions are better positioned now. However, there are still areas for improvement, such as content quality, leadership from medical institutions, and readability of information. References: Suarez-Almazor et al. Surfing the Net–information on the World Wide Web for persons with arthritis: patient empowerment or patient deceit? J Rheumatol 2001;28:185–91. Disclosure of Interest: None declared